Validation of a Loop-Mediated Isothermal Amplification Assay for Rapid Diagnosis of Invasive Pneumococcal Disease - de Paz, Héctor David; Brotons, Pedro; Esteva, Cristina; Muñoz-Almagro, Carmen (Frontiers in Cellular and Infection Microbiology, 2020)
Current molecular PCR-based techniques used for detecting Streptococcus pneumoniae, the causative pathogen of invasive pneumococcal disease (IPD), are accurate but have a run time of several hours. We aimed to develop and validate a novel real-time loop mediated amplification (LAMP) assay for rapid detection of pneumococcus in normally sterile samples with accuracy comparable to a gold standard real-time PCR. Conserved regions of lytA were used for the design of the LAMP test. Analytical validation included assessment of linearity, limit of detection (LOD), intra-assay and inter-assay precision and analytical specificity, which was evaluated by using reference strain S. pneumoniae R6 and a quality control panel. Clinical performance was assessed on all samples collected from children with suspicion of IPD attended in Hospital Sant Joan de Deu (Barcelona, Spain) during the period April-September 2015. Fresh samples were analyzed after DNA extraction. The following values of analytical parameters were determined: linearity within the range 108-104 copies/mL; limit of detection, 5·103 copies/mL; intra- and inter-assay precision measured by mean coefficient of variance, 3.61 and 6.59%; analytical specificity, 9/9 pathogens similar to S. pneumoniae and 14/14 strains of different S. pneumoniae serotypes correctly identified as negative and positive results, respectively. Diagnostic sensitivity and specificity values were 100.0 and 99.3%. Median time of DNA amplification was 15 min. The new LAMP assay showed to have similar accuracy as PCR while being 5-fold faster and could become a useful diagnostic tool for early diagnosis of IPD.